Data Resource Profile: The Mental Health of Children and Young People (MHCYP) 2017 and follow-up surveys - Karimipour, Mohammad; Barker, Harry; Newlove-Delgado , Tamsin; Downs, Johhny; McManus, Sally; Marcheselli, Franziska; Penhallow, Jessica; Cross, Lauren; Baser, Aslihan; Mathews, Frances; Faria, Clara; Ford, Tamsin (International Journal of Population Data Science, 2026)
Introduction Amid growing global concern about child and adolescent mental health problems and their long-term consequences, research in this area is increasingly critical. Population-representative datasets are valuable resources for addressing these challenges. The Mental Health of Children and Young People (MHCYP) 2017 survey was designed to meet this need in England. Methods The 2017 survey included 9117 children and young people aged 2 to 19 years. Information was collected from parents or carers (hereafter referred to as 'parents'), and for those aged 11 years or over, directly from the young people themselves, as well as from teachers. The baseline assessment used the standardised Development and Wellbeing Assessment (DAWBA), based on ICD-10 and DSM-5 diagnostic criteria. The subsequent waves in 2020, 2021, 2022 and 2023, measured mental health difficulties using the Strengths and Difficulties Questionnaire (SDQ). Results The MHCYP 2017 survey and its follow-up waves provide population-representative data on children and adolescents in England, encompassing a range of mental health disorders and difficulties---from eating disorders and attention and hyperactivity disorder to depression and anxiety, with longitudinal data on mental health, social situation and activities during the Covid-19 pandemic. It builds on earlier UK representative surveys conducted in 1999 and 2004. Conclusion Together with the 1999 and 2004 surveys, this dataset offers a unique opportunity to investigate trends in mental health disorders among young people, assess associated difficulties and comorbidities, and explore links with socio-economic factors. The MHCYP 2017 survey and follow-ups offer valuable cross-sectional data for understanding child and adolescent mental health trends in the UK, with longitudinal data from four subsequent surveys conducted between 2020 and 2023.